The Soul of Learning - Sterling, Dorothy ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Despite current emphasis on racial problems, few books present honestly the Negro experience in the United States. Adolescents' and children's books portraying Negroes in realistic situations have increased over the past two decades, but they comprise only 1% of the total output of books for young people. Textbooks that include Negroes or Negro culture are few. In recent years, some attempt has been made to integrate reading primers, but most history texts are still "disappointingly full of misstatements, omissions, and bias." To remedy this situation, publishers should actively encourage new books by and about Negroes that candidly present contemporary life. Also, teachers can help emphasize Negro experience through creative teaching. A semester's "exploration of soul," the reading of Negro literature, or the writing of a term paper on racial problems can all contribute to a better understanding of the Negro's, and conversely the white man's, history and role in America. (Many books involving Negroes are cited throughout the article.) (LH)
ERIC Note: Speech given at the NDEA Institute in English, Univ. of Wisconsin, Milwaukee, Summer 1967.
English Journal, v57 n2 p166-80 Feb 1968.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Achievement; Black Attitudes; Black Community; Black Culture; Black Education; Black History; Black Influences; Black Leadership; Black Youth; Blacks; English Instruction; Literature; Publishing Industry; Racial Attitudes; Racial Discrimination; Racial Identification; Racial Integration; Racial Relations; Teaching; Textbook Bias